Addiction to social networks and aggression in teenegers in the province of San Martin - Roque Rengifo, Diana Olimpia (2022)
Objective: To determine the relationship between the level of risk of addiction to social networks withaggressive behavior in adolescents. Methodology: Quantitative approach, non-experimental design,correlational and cross-sectional type, the sample was obtained by demonstrated non-probabilisticconvenience sample of 300 students between men and women between 11 and 15 years of age, datacollection was performed virtually through the Google forms platform. Addiction to Social Networks(ARS) and the Aggression Questionnaire (AQ) were used for data collection. Results: High levels ofaggressive behavior were found with 26.0% in the students and it was found among the describedvariables it turned out to be statistically significant (0.000) with a (.242**). Conclusion: Finding thatadolescent students, the more they use social networks, the more likely they are to manifest behaviorsthat involve aggression (p>0.05).